2019
DOI: 10.1186/s13765-019-0412-x
|View full text |Cite
|
Sign up to set email alerts
|

Geraniin ameliorate experimental acute reflux esophagitis via NF-κB regulated anti-inflammatory activities in rats

Abstract: Repeated reflux of gastric acid and stomach contents into the esophagus leads to esophagus damage, including inflammation, ulcer, and hemorrhage in the epithelium. In this study, we aimed to demonstrate the ameliorating effects of geraniin, a phytochemical in the geraniums, on esophagus damage in an acute reflux esophagitis (RE) rat model. The inflammatory effects of geraniinwas measured by nitric oxide (NO) production and pro-inflammatory protein levels in lipopolysaccharide (LPS)-induced RAW 264.7 cells. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…Long-lasting inflammation raises the risk of chronic disease. Nitric oxide (NO) is a pro-inflammatory mediator that induces inflammation due to overproduction in abnormal situations. , Prior research has indicated that iridoids exhibit promising anti-inflammatory activity . Therefore, the secoiridoids isolated from S. dilatata flowers were assayed for their potential to suppress NO production in LPS-provoked RAW 264.7 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Long-lasting inflammation raises the risk of chronic disease. Nitric oxide (NO) is a pro-inflammatory mediator that induces inflammation due to overproduction in abnormal situations. , Prior research has indicated that iridoids exhibit promising anti-inflammatory activity . Therefore, the secoiridoids isolated from S. dilatata flowers were assayed for their potential to suppress NO production in LPS-provoked RAW 264.7 cells.…”
Section: Resultsmentioning
confidence: 99%
“…IκB-α is a factor that mediates the activity of NF-κB, which modulates immune and inflammatory responses and plays a vital role in inflammation and immunity. In particular, it has been reported that IκB-α and NF-κB play an important role in the maintenance of esophageal microenvironment homeostasis (Nam, 2019; Baldwin, 2001). Phosphorylation of IκB-α and NF-κB in the esophageal epithelium has been reported to exacerbate esophageal inflammation, which promotes the secretion of various inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Geraniin found in geraniums can ameliorate experimental acute reflux esophagitis via NF-κB-regulated anti-inflammatory activities in rats [178,179]. It (15-20 µM) can also suppress TGF-1-induced EMT, migration, invasion and anoikis resistance in A549 lung cancer cells [180].…”
Section: Reversal Of Emt By Anti-inflammatory Natural Compoundsmentioning
confidence: 99%